Distibution of Wood-borers in the Vembanad Backwaters - N., Balakrishnan Nair (Fishery Technology, 2025)
The nature of destruction of cellulose mateials in the Vembanad backwaters has been examined. Teredinids such as Lyrodus pedicellatus, L. massa, Teredo furcifera, Nausilora hedleyi and Bankia carinata; pholads namely, Martesia strkla and Lignopholas lumimlis and sphaeromatids like Sphaeroma terebrans and S. anmndalei were the wood-borers. The molluscs and crustaceans were represented almost equally, damaging timber in the region north of the Thanneermukkam bund. The incidence and relative abundance of these pests are discussed in relation to the salinity profile of the estuary.